Bedside counseling on complementary medicine as a new model in pediatric cancer care—protocol of the SiKOM multicenter prospective cohort study - Lara Nowak; Daniela Reis; Rebecca Büttner; Melanie Schwermer; Jennifer Bals; David D. Martin; David D. Martin; Thomas Ostermann; Alfred Längler; Alfred Längler; Heidemarie Haller; Tycho Zuzak; et al. (Frontiers in Pediatrics)
IntroductionAn open dialogue between parents of children with cancer and medical staff about the benefits, risks, and interactions of complementary medicine used during cancer treatment is essential to enhance treatment safety and efficacy. However, both parents and medical staff often lack sufficient knowledge and willingness to engage in such discussions. To address this, bedside counseling for patients and families is proposed, provided directly by an external team comprising experienced specialists in complementary and conventional medicine. This approach aims to facilitate communication, improve understanding, and mitigate risks associated with complementary medicine during pediatric cancer care.MethodsThis study will be conducted in five pediatric cancer centers in Germany. Physicians specializing in complementary medicine and pediatric oncology will provide bedside counseling to patients, parents, and local medical staff. Feasibility and change measures will be evaluated by comparing cohorts of parents who received complementary medicine counseling with those who did not, as well as medical staff before and after training sessions. Semi-structured interviews with parents and medical staff will further explore barriers to complementary medicine counseling and identify strategies to enhance its implementation. Quantitative data will be analyzed to assess the feasibility of the intervention, while qualitative data will provide in-depth insights into the perspectives and experiences of stakeholders.ResultsThe results will highlight predictors for effective, use-oriented counseling tailored to different target groups. This prototype support care model will serve as a framework for implementing complementary medicine counseling both within and beyond inpatient pediatric oncology settings. By integrating these findings, we aim to develop a replicable approach to complementary medicine counseling that addresses the unique needs of pediatric cancer patients, their families, and medical professionals.DiscussionPrevious initiatives have primarily focused on training individual physicians within each center to address complementary medicine. In contrast, this novel strategy emphasizes direct bedside counseling for pediatric patients and families while providing ongoing support to local staff. This approach seeks to enhance treatment safety by reducing unintended interactions between complementary medicine and conventional cancer therapies, ultimately improving care quality and patient outcomes.Trial RegistrationGerman Clinical Trials Register (DRKS), ID: DRKS00030478. Registered 22 December 2022 https://www.drks.de/DRKS00030478.